2015
DOI: 10.1097/sla.0000000000000797
|View full text |Cite
|
Sign up to set email alerts
|

En Bloc Resection of Pulmonary Sulcus Non-small Cell Lung Cancer Invading the Spine

Abstract: Multimodality therapy including en bloc resection for pulmonary sulcus NSCLC invading the spine provides excellent long-term survival in selected patients. This result establishes a benchmark against which the effects of new treatments can be compared in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 13 publications
1
28
3
Order By: Relevance
“…77 This appears to be far superior to the 26-27% 5-year survival reported in studies reporting intralesional or not en-bloc resection. [77][78][79] The only significant predictor of survival was R0 resection. There was a high rate of R0 resection (89%) compared with 9% R1 (positive microscopic margin) and 2% R2 (positive macroscopic margin).…”
Section: Pulmonary Sulcus Tumours With Spine Invasionmentioning
confidence: 75%
See 4 more Smart Citations
“…77 This appears to be far superior to the 26-27% 5-year survival reported in studies reporting intralesional or not en-bloc resection. [77][78][79] The only significant predictor of survival was R0 resection. There was a high rate of R0 resection (89%) compared with 9% R1 (positive microscopic margin) and 2% R2 (positive macroscopic margin).…”
Section: Pulmonary Sulcus Tumours With Spine Invasionmentioning
confidence: 75%
“…All 135 patients had en-bloc resection of lung, spine and chest wall. 77 Pooled analysis showed that 5-and 10-year OS were 43% and 26%, respectively. 77 This appears to be far superior to the 26-27% 5-year survival reported in studies reporting intralesional or not en-bloc resection.…”
Section: Pulmonary Sulcus Tumours With Spine Invasionmentioning
confidence: 99%
See 3 more Smart Citations